Transcatheter mitral valve-in-valve implantation: a 10-year single center experience. (14th October 2021) - Akodad, M; Sathananthan, G; Chatfield, A G; Trpkov, C; Lounes, Y; Chuang, A; Wood, D A; Boone, R H; Moss, R; Cheung, A; Ye, J; Blanke, P; et al.
Abstract: Background: Transcatheter mitral valve-in-valve (TMVIV) appears a reasonable alternative to surgical redo mitral valve replacement in patients with degenerated mitral prosthesis and high surgical risk with favorable early and mid-terms outcomes. Long-term outcomes are limited by high mortality in a comorbid population. Purpose: We aimed to evaluate early prosthesis hemodynamic performance and late clinical outcomes following TMVIV. Methods: All patients who underwent TMVIV for degenerated surgical mitral bioprostheses from 2011 to 2020 in our center were included. Prospectively collected demographic, clinical, procedural, and imaging variables were analyzed. Clinical and echocardiographic outcomes were defined according to Mitral Valve Academic Research Consortium (MVARC) definitions and assessed at 30-day and at the latest follow-up available. Results: A total of 67 patients were included; mean age 76.9±9.6 years, mean STS score 11.0±6.2%, 53.7% male (n=36). Mechanisms of bioprosthetic failure were mitral stenosis (n=32, 47.8%), mitral regurgitation (n=24, 35.8%), and mixed (n=11, 16.4%). Mean time from mitral valve surgery to TMVIV was 10.2±4.3 years. Access was mostly transapical (n=45; 67.2%), followed by transseptal (n=22; 32.8%). Following the first transseptal procedure in 2016; transseptal access accounted for the majority of procedures (22 of 37 cases, 59.4%). Technical success was achieved in 65 patients (97.0%). Mean hospitalization was 9.2±10.0 days; shorter with the transseptal as opposed to the transapical approach (6.3±8.1 days versus 11.0±10.5 days, p=0.001). At 30-day echographic follow-up, mean mitral valve gradient was 7.3±2.7 and 1 patient (1.9%) had mitral regurgitation >mild. At 30-day follow-up, 3 patients had died (4.5%); due to left ventricular outflow tract obstruction (1), heart failure (1), and stroke (1). New pacemakers were required in 2 patients (3.0%) and pacemaker lead dislodgement occurred in 1 patient (1.5%), 4 patients (6.2%) were hospitalized for heart failure. At a median follow-up of 3.8 years [1.7–5.1], 29 patients had died (43.3%), valve thrombosis was found in 6 (8.9%) and endocarditis in 4 patients (6.2%). Mitral valve reintervention was performed in 4 patients (6.2%); redo TMVIV due to valve migration in 1 (1.9%), surgical valve replacement in 1 (1.9%), and delayed redilation with a non-compliant balloon due to underexpansion in 2 patients (3.8%). Conclusion: TMVIV is associated with acceptable 30-day mitral valve hemodynamics. Long-term mortality remains high in this high-surgical risk comorbid group. Funding Acknowledgement: Type of funding sources: None.